2021
DOI: 10.2196/26242
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Broadband and Use of Telehealth Among Older Adults: Cross-sectional Study of National Survey Data Linked With Census Data

Abstract: Background The COVID-19 pandemic has amplified the role of telehealth in health care delivery. Regional variation in internet access and telehealth use are well-documented, but the effect of neighborhood factors, including the pervasiveness of broadband internet, on older adults’ telehealth usage in the context of internet access is not known. Objective This study aimed to investigate how individual and neighborhood characteristics, including the pervas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…It is unclear why that may be the case, but the greater rate of unemployment among the lower income group may provide them with more time. Notably this is a group of individuals who elected to pursue telemental health platform for their care, so this particular group of lower income individuals were obviously able to access it, which may not be the case for some ( 33 ). However, a recent study, in accordance with this sample, found that people with lower incomes (less than $25,000 annually) were more likely to use telehealth services during the pandemic than people with higher incomes ( 34 ) suggesting that telehealth increases access for lower income individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why that may be the case, but the greater rate of unemployment among the lower income group may provide them with more time. Notably this is a group of individuals who elected to pursue telemental health platform for their care, so this particular group of lower income individuals were obviously able to access it, which may not be the case for some ( 33 ). However, a recent study, in accordance with this sample, found that people with lower incomes (less than $25,000 annually) were more likely to use telehealth services during the pandemic than people with higher incomes ( 34 ) suggesting that telehealth increases access for lower income individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the pandemic and the increasing use of technology by society in general during this unprecedented event. Engagement with telehealth may be more a factor of socioeconomic status (i.e., broadband access) than age ( 40 ). Even if older adults prefer “in person“ care (not addressed by this study), the results of this study suggest that they can nonetheless benefit from them.…”
Section: Discussionmentioning
confidence: 99%
“…The use of electronic patient portals raises challenges and ethical issues regarding older adults. Notably, disparities in internet access, a key factor for the use of e-health, persist among underserved populations such as older adults and individuals of lower socioeconomic status [ 52 , 53 ]. Older adults may encounter more challenges in the use of EHR and electronic patient portals because older generations must learn and acquire the necessary skills needed to navigate the internet and are less comfortable using technology compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%